Association of the Endothelial Activation and Stress Index (EASIX) with Clinical Outcomes in Patients with Pneumosepsis: A Retrospective Cohort Study - Derya Özyiğitoğlu; Ayşe Çapar; Emre Çapar; Şeyma Başlılar (Life, 2026)
Background: Endothelial dysfunction is a key component of sepsis pathophysiology. The Endothelial Activation and Stress Index (EASIX) is a practical biomarker derived from routine laboratory parameters and indirectly reflects endothelial injury. This study aimed to evaluate the prognostic association of EASIX with in-hospital mortality and organ-support requirements among patients with pneumosepsis admitted to the intensive care unit (ICU). Methods: This retrospective cohort study included 1787 adult patients with pneumosepsis admitted to a tertiary ICU from January 2018 to December 2025. EASIX was calculated from laboratory parameters obtained at ICU admission, and log2-EASIX was used in all analyses. The primary outcome was in-hospital mortality. Secondary outcomes included the need for invasive mechanical ventilation (IMV), vasopressor therapy within the first 24 h, second-line vasopressor therapy, and continuous renal replacement therapy (CRRT) within the first 7 days after ICU admission. Associations with the primary and secondary outcomes were evaluated using univariable and multivariable logistic regression, and discriminative performance was assessed using receiver operating characteristic (ROC) curve analysis. Results: The in-hospital mortality rate was 56.2%. Log2-EASIX was independently associated with in-hospital mortality (OR: 1.191, 95% CI: 1.119–1.268; p < 0.001). ROC analysis showed moderate discrimination for predicting in-hospital mortality (AUC: 0.673, 95% CI: 0.648–0.698), with a ROC-derived exploratory cut-off of 1.47. Patients with log2-EASIX ≥ 1.47 had approximately a two-fold higher risk of in-hospital mortality (OR: 2.039, 95% CI: 1.610–2.584; p < 0.001). In multivariable analyses of the secondary outcomes, log2-EASIX remained independently associated with second-line vasopressor requirement (adjusted OR: 1.104, 95% CI: 1.040–1.171; p = 0.001) and CRRT requirement within 7 days (adjusted OR: 1.317, 95% CI: 1.236–1.404; p < 0.001). However, its associations with IMV and initial vasopressor requirements were not statistically significant after adjustment. Adding log2-EASIX to the Acute Physiology and Chronic Health Evaluation (APACHE) II resulted in a statistically significant but small improvement in discrimination compared with APACHE II alone (AUC: 0.761 vs. 0.740; ΔAUC = 0.021; 95% CI: 0.010–0.032; p < 0.001). Conclusions: EASIX was independently associated with in-hospital mortality and second-line vasopressor requirement, and it remained associated with CRRT requirement after multivariable adjustment. However, serum creatinine alone showed superior discrimination for CRRT, suggesting that the association between EASIX and CRRT may be driven, at least in part, by its creatinine component and should therefore be interpreted cautiously. In contrast, the associations of EASIX with early IMV and initial vasopressor requirements were not significant after multivariable adjustment. Although its discriminative performance for mortality was moderate when used alone, EASIX may provide complementary prognostic information when added to established disease severity assessment. These findings warrant validation in prospective, multicenter studies.